Maternal Nicotine Exposure Leads to Impaired Disulfide Bond Formation and Augmented Endoplasmic Reticulum Stress in the Rat Placenta - Wong, Michael K. (PLoS One, 2015)
Maternal nicotine exposure has been associated with many adverse fetal and placental outcomes. Although underlying mechanisms remain elusive, recent studies have identified that augmented endoplasmic reticulum (ER) stress is linked to placental insufficiency. Moreover, ER function depends on proper disulfide bond formation—a partially oxygen-dependent process mediated by protein disulfide isomerase (PDI) and ER oxidoreductases. Given that nicotine compromised placental development in the rat, and placental insufficiency has been associated with poor disulfide bond formation and ER stress, we hypothesized that maternal nicotine exposure leads to both placental ER stress and impaired disulfide bond formation. To test this hypothesis, female Wistar rats received daily subcutaneous injections of either saline (vehicle) or nicotine bitartrate (1 mg/kg) for 14 days prior to mating and during pregnancy. Placentas were harvested on embryonic day 15 for analysis. Protein and mRNA expression of markers involved in ER stress (e.g., phosphorylated eIF2α, Grp78, Atf4, and CHOP), disulfide bond formation (e.g., PDI, QSOX1, VKORC1), hypoxia (Hif1α), and amino acid deprivation (GCN2) were quantified via Western blot and/or Real-time PCR. Maternal nicotine exposure led to increased expression of Grp78, phosphorylated eIF2α, Atf4, and CHOP (p<0.05) in the rat placenta, demonstrating the presence of augmented ER stress. Decreased expression of PDI and QSOX1 (p<0.05) reveal an impaired disulfide bond formation pathway, which may underlie nicotine-induced ER stress. Finally, elevated expression of Hif1α and GCN2 (p<0.05) indicate hypoxia and amino acid deprivation in nicotine-exposed placentas, respectively, which may also cause impaired disulfide bond formation and augmented ER stress. This study is the first to link maternal nicotine exposure with both placental ER stress and disulfide bond impairment in vivo, providing novel insight into the mechanisms underlying nicotine exposure during pregnancy on placental health.